Pengaruh pendampingan suami terhadap tingkat kecemasan pada proses persalinan ibu primigravida kala 1 - Ita Novita Sari; Ernita Prima Noviyani; Ageng Septarini (THE JOURNAL OF Mother and Child Health Concerns, 2021)
Background: In Indonesia, there are 373,000,000 pregnant women, of which there are 107,000,000 pregnant women who experience anxiety in facing childbirth. And on the island of Java in 2018 pregnant women who experienced anxiety in childbirth found 35,587 people (52.3%). Purpose: This study aims to determine the comparison of the influence of husband's assistance on the level of anxiety in the labor process of first-stage primigravida mothers at public health center Pulosari, Pandeglang Regency in 2022. Methods: This study used an observational analytic study with a cross sectional approach with a sample of 60 primigravida mothers in the first stage which were divided into 2 groups, namely the group of mothers who were accompanied by their husbands and the group of mothers who were not accompanied by their husbands and the research instrument used an anxiety questionnaire from Hamilton Anxiety Rating Scale (HARS) and husband assistance questionnaire. Results: The results of the study obtained a P Value of 0.000 <0.05. This indicates that there is an influence of husband's assistance on the level of anxiety in the labor process of first-stage primigravida mothers at technical implementation unit Pulosari Health Center. Husband's assistance during childbirth has a great influence in reducing maternal anxiety, so that all forms of support during mentoring from the beginning to the end of labor can provide positive suggestions so that the delivery process goes smoothly, the mother and baby are healthy and safe. Pendahuluan: Di  Indonesia  tercatat dari  373.000.000  orang  ibu  hamil, diantaranya terdapat 107.000.000 orang ibu hamil yang  mengalami  kecemasan  dalam  menghadapi persalinan. Dan di  pulau  Jawa  pada  tahun  2018 ibu hamil yang mengalami kecemasan dalam persalinan berjumlah 35.587 orang (52,3%). Tujuan: Penelitian ini bertujuan untuk mengetahui perbandingan pengaruh pendampingan suami terhadap tingkat kecemasan pada proses persalinan ibu primigravida kala 1 di UPT Puskesmas Pulosari Kabupaten Pandeglang tahun 2022. Metode: Penelitian ini menggunakan penelitian analitik observasional dengan pendekatan cross sectional dengan jumlah sampel sebanyak 60 ibu bersalin primigravida kala I yang dibagi menjadi 2 kelompok yaitu kelompok ibu bersalin yang didampingi oleh suami dan kelompok ibu bersalin yang tidak didampingi oleh suami serta instrumen penelitian menggunakan kuisioner kecemasan   dari Hamilton   Anxiety   Rating   Scale (HARS) dan kuesioner pendampingan suami. Hasil: Hasil penelitian diperoleh nilai P Value 0,000 <0,05 ini menunjukan bahwa ada pengaruh pendampingan suami terhadap tingkat kecemasan pada proses persalinan ibu primigravida kala 1 di UPT Puskesmas Pulosari. Pendampingan suami pada saat proses persalinan memiliki pengaruh yang besar dalam mengurangi kecemasan ibu bersalin, sehingga semua bentuk support selama pendampingan dari awal hingga akhir persalinan dapat memberikan sugesti positif sehingga proses persalinan lancar, ibu dan bayi sehat selamat.